The role of expert focus echocardiography during the COVID‐19 pandemic. Issue 5 (17th April 2022) - McPhail, Eleanor; Jahagirdar, Nishat; Walker, Nicola; Harris, Scott; Monaghan, Mark; Papachristidis, Alexandros
Abstract: Background: Focus Echocardiography has routinely been used to offer quick diagnosis in critical care environments, predominantly by clinicians with limited training. During the COVID‐19 pandemic, international guidance recommended all echocardiography scans were performed as focus studies to limit operator viral exposure in both inpatient and outpatient settings. The aim of this study was to assess the effectiveness of eFoCUS, a focus scan performed by fully trained echocardiographers following a minimum dataset plus full interrogation of any pathology found. Methods: All diagnostic echocardiograms, performed by fully trained echocardiographers during an 8‐week period during the first UK COVID‐19 wave, were included. The number of images acquired was compared in the following categories: admission status, COVID status, image quality, indication, invasive ventilation, pathology found, echocardiographer experience, and whether eFoCUS was deemed adequate to answer the clinical question. Results: In 87.4% of the 698 scans included, the operator considered that the eFOCUS echo protocol, with additional images when needed, was sufficient to answer the clinical question on the request. Echocardiographer experience did not affect the number of images acquired. Less images were acquired in COVID‐19 positive patients compared to negative/asymptomatic (38 ± 12 vs. 42 ± 12, p = .001), and more images were required when a valve pathology was identified. Conclusion: eFoCUS echocardiography is an effective protocol for use during the COVID‐19 pandemic. It provides sufficient diagnostic information to answer the clinical question but differs from standard focus/limited protocols by enabling the identification and interrogation of significant pathology and incidental findings, preventing unnecessary repeat scans and viral exposure of operators.